2012
DOI: 10.1271/bbb.120021
|View full text |Cite
|
Sign up to set email alerts
|

A New Prenylflavonoid Isolated from Propolis Collected in the Solomon Islands

Abstract: The new prenylflavonoid, solophenol A (1), together with three known compounds, bonannione A (2), sophoraflavanone A (3) and (2S)-5,7-dihydroxy-4'-methoxy-8-prenylflavanone (4), were isolated from propolis collected from Malaita Island in The Solomon Islands. The structure of each compound was determined by spectroscopic methods, including mass spectrometry and 2D NMR. Compound 1 exhibited potent 2,2-diphenyl-1-picrylhydrazyl radical-scavenging activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…According to the geographical origin and the typical chemical compounds, the botanical origins of these propolis samples are assumed to be the genus Populus. In samples from the Solomon Islands and Kenya, researchers identified four flavonols 6 – 9 and confirmed that these compounds exhibited potent antibacterial activity [31]. The majority of the identified compounds were also found in the plants Macaranga , suggesting that the genus Macaranga is the likely plant source.…”
Section: Flavonoidsmentioning
confidence: 95%
See 1 more Smart Citation
“…According to the geographical origin and the typical chemical compounds, the botanical origins of these propolis samples are assumed to be the genus Populus. In samples from the Solomon Islands and Kenya, researchers identified four flavonols 6 – 9 and confirmed that these compounds exhibited potent antibacterial activity [31]. The majority of the identified compounds were also found in the plants Macaranga , suggesting that the genus Macaranga is the likely plant source.…”
Section: Flavonoidsmentioning
confidence: 95%
“…Macaranga schweinfurthii is the only plant source of these two geranylstilbenes to this date [37]. In 2012, another stilbene, 5-farnesyl-3'-hydroxyresveratrol ( 190 ) was identified in Solomon Island propolis, which is also present in Macaranga plants [31]. These results suggest that Macaranga is probably the plant source of the propolis from Kenya and Solomon Island.…”
Section: Phenolicsmentioning
confidence: 99%
“…Prenylated flavanone-type compounds, which were previously classified as a chemical marker of Pacific HBP, have been found not only in Asia (Japan [ 75 , 85 ], Oman [ 125 ], and Taiwan [ 70 , 84 ]), and Oceania (Fiji [ 143 ] and Solomon Island [ 106 , 117 , 118 ]), but also in Africa (Egypt [ 92 , 100 ] and Nigeria [ 141 ]). These compounds originated from Macaranga spp.…”
Section: Propolis Components: Chemistry and Geographical Distributmentioning
confidence: 99%
“…Propolis, collected from the Solomon Islands, a country in the southwestern Pacific Ocean close to northeastern Australia, was analyzed in 2010 and four primary prenylflavonoids—NA, NB, NC, and GN—were found (Raghukumar et al, 2010). In a later study, three other prenylflavonoids—bonannione A, sophoraflavanone A, and (2 S )‐5,7‐dihydroxy‐4′‐methoxy‐8‐prenylflavanone—were purified by propolis from the Solomon Islands (Inui et al, 2012). Since most of the compounds found in propolis from the Solomon Islands are similar to those in Macaranga plants, the genus, Macaranga , is thought to be the probable plant source (Huang et al, 2014).…”
Section: Chemical Constituents and Plant Sources Of Macaranga‐type Prmentioning
confidence: 99%
“…Recent studies revealed that propolis from other regions, such as Egypt, Kenya, and the Solomon Islands, also contain Macaranga spp. ingredients (Huang, Zhang, Wang, Li, & Hu, 2014; Inui et al, 2012; Petrova et al, 2010; Salatino, Fernandes‐Silva, Righi, & Salatino, 2011). Thus, all propolis derived from Macaranga spp.…”
Section: Introductionmentioning
confidence: 99%